Decision Support System for Land Suitability in Percut Sei Tuan District - Suci Hasti; Achwil Putra Munir; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Land use that is not according to his ability, besides causing damage to the land, will also increase the problem of poverty and other social problem, can even destroy a culture that had been evolving. Due to the problem of agricultural land and the farmer’s need for information and knowledge to determine the types of plants that is suitable to the characteristic’s of land, an information system is needed as a decision support system in order to determine the feasibility of land for planting a commodity. Decision Support System for Land Suitability in Percut Sei Tuan District was made using the right matching method. From the results, it was known that in Kenangan and Kenangan Baru land were not suitable for the five commodities to be planted based on history of planting in the area. However there were some areas with the level of 5 high main parameters, but do not guarantee that the land would produces well, based on the history of plant productivity that can be rely on by the surrounding community for several years. Keywords: decision support system, land suitability, matching methods